Propuesta de rediseño de procesos de la unidad de talento humano del Gobierno Autónomo Descentralizado del cantón Sucre - Rosado Cedeño, María Tahiryn (2022)
The objective of this research is to propose a process redesign of the Human Talent Unit of the Decentralized Autonomous Government in Sucre canton. The methodology was organized in three phases: in the first, the representation of the processes was developed by means of cards and the AS IS diagram to identify them; in the second, the improvement of processes was developed, with the application of the Added Value Analysis (AVA), establishing the indicators for each one of them; finally, in the third phase, the redesign of the processes and procedures manual was carried out. The main results of this research are focused on the detection of six processes not identified in the current manual; the application of the AVA established that the efficiency of the processes ranges between 55.56% and 80%. In this sense, the proposal for the redesign of the Manual of Processes and Procedures of the Human Talent Unit of the GAD in Sucre canton showed that the improvements increase efficiency by 100%.